Analisis Produktivitas Electrolytic Tinning Line dengan Metode Overall Equipment Effectiveness dan Penentuan Kebutuhan Sparepart Komponen Mekanikal Kritis dengan Pendekatan ABC - Ramadhania, Sherin; Iqballulah, Iqballulah; Mislan, Mislan (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
A company that produces high quality tinplate with international standards. The product produced is tinplate, namely steel sheets coated with tin. In ETL downtime from May 2022 – April 2023, there is a gap between actual and target downtime, causing the production process to not run optimally, and will cause losses for the company. So it is necessary to determine the effectiveness value of the equipment in ETL and determine the need for spare parts for critical mechanical components. OEE is the magnitude of the effectiveness value of equipment or machines in the Company. ABC classification is a classification of a group of materials in descending order based on the cost of using the material per time period. The results of data processing obtained an average OEE value of 80.06% and for items in class A it was a mechanical seal sink roll. Items in class B are solenoid valve – 48VDC and scotch brite and items in class C are mechanical seal DN 45, filter regulator, bearing 7308DB, bearing NU308EC, and hose assembly.